1985
DOI: 10.1016/s0735-1097(85)80423-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative regression of left ventricular dimensions in aortic insufficiency: A long-term echocardiographic study

Abstract: The ability of preoperative M-mode echocardiography to predict the clinical course and the decrease in left ventricular size was assessed in 42 patients after uncomplicated valve replacement for isolated aortic insufficiency. During follow-up study, one patient died of chronic heart failure. The New York Heart Association functional class of the 41 survivors improved from 2.4 to 1.2. All patients had a preoperative M-mode echocardiogram. Serial echocardiographic measurements, available in 33 patients, showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[235][236][237][238][239][240][241][242][243][244][245][246] With time, during which the ventricle develops progressive chamber enlargement and a more spherical geometry, depressed myocardial contractility predominates over excessive loading as the cause of progressive systolic dysfunction. This can progress to the extent that the full benefit of surgical correction of the regurgitant lesion, in terms of recovery of LV function and improved survival, can no longer be achieved.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[235][236][237][238][239][240][241][242][243][244][245][246] With time, during which the ventricle develops progressive chamber enlargement and a more spherical geometry, depressed myocardial contractility predominates over excessive loading as the cause of progressive systolic dysfunction. This can progress to the extent that the full benefit of surgical correction of the regurgitant lesion, in terms of recovery of LV function and improved survival, can no longer be achieved.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Previous studies demonstrated that persistent ventricular dilatation and dysfunction identifies patients at risk of death from congestive heart failure. 17, 19 Recently, operative mortality and overall survival was shown to decline after AVR in a high-risk group. Therefore, we prefer surgical correction over medically conservative care even in high-risk patients.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…In spite of the anatomical proximities and the pathological functioning [42][43][44][45][46][47][48][49][50][51] that urged our study to analyze the correlation between the right atrium and the tricuspid valve, the right ventricle and the pulmonary valve, the left atrium and the mitral valve, and the left ventricle and the aortic valve, our results did not display any correlation. This outcome could be explained by two hypotheses.…”
Section: Discussionmentioning
confidence: 69%